2003
DOI: 10.1029/2002rs002802
|View full text |Cite
|
Sign up to set email alerts
|

HYCELL—A new hybrid model of the rain horizontal distribution for propagation studies: 1. Modeling of the rain cell

Abstract: [1] From radar observations of rain fields at midlatitudes, a new physical model of rain cells is proposed. It strives to describe optimally the rain rate horizontal distribution within rain cells down to 1 mm h À1 . The approach is similar to that of the well-known EXCELL model. The mathematical definition of the model lies in the combination of a gaussian function and an exponential one, the cells having an elliptic horizontal cross section. Due to its hybrid structure, the new model has been named HYCELL. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 20 publications
2
84
0
Order By: Relevance
“…Considering a database of 213 112 rain cells identified at t = R 2 = 1 mm h À1 from the radar of Météo-France at Bordeaux in 1996 (southwestern France, midlatitude oceanic climate), and another database composed of 701 882 cells observed at the same threshold from the radar of Karlsruhe in 1999 (southwestern Germany, midlatitude continental climate), Féral et al [2003] have shown that, whatever the climatology, the HYCELL model enables one to improve the description of the rain rate horizontal distribution within the cells with respect to the well-known EXCELL model [Capsoni et al, 1987b].…”
Section: Hybrid Modeling Of the Rain Cell Horizontalmentioning
confidence: 99%
See 4 more Smart Citations
“…Considering a database of 213 112 rain cells identified at t = R 2 = 1 mm h À1 from the radar of Météo-France at Bordeaux in 1996 (southwestern France, midlatitude oceanic climate), and another database composed of 701 882 cells observed at the same threshold from the radar of Karlsruhe in 1999 (southwestern Germany, midlatitude continental climate), Féral et al [2003] have shown that, whatever the climatology, the HYCELL model enables one to improve the description of the rain rate horizontal distribution within the cells with respect to the well-known EXCELL model [Capsoni et al, 1987b].…”
Section: Hybrid Modeling Of the Rain Cell Horizontalmentioning
confidence: 99%
“…[12] Féral et al [2003] proposed to describe the rain rate horizontal distribution (RRHD) within rain cells having an elliptic horizontal cross section by combining a gaussian component with an exponential one (Figure 1), so that the analytical expression of the RRHD becomes, in the horizontal plane (Oxy):…”
Section: Hybrid Modeling Of the Rain Cell Horizontalmentioning
confidence: 99%
See 3 more Smart Citations